DIGITALIZATION AS A FACTOR OF DEVELOPMENT OF ENTERPRISE PERSONNEL - Polyanska , A.S.; Kinash, I.P.; Savchuk , S.V. (The actual problems of regional economy development, 2019)
The article deals with the relevance, prerequisites and directions of training and development of personnel in terms of digitalization in domestic practice. The concept of “knowledgeworker” and the characteristics of such employee's activity have been clarified (the main factors that determine the productivity of the personnel having special knowledge in their profession are given), the role of “knowledge worker” is defined. The concepts of “digital literacy” and “digital competence” are described as important characteristics of new knowledge. Prerequisites for digitalization at domestic enterprises are analyzed. The dynamics of the use of information and communication technologies at enterprises is investigated. Indicators were analyzed: the share of enterprises using computers by industry and the share of the average number of workers using the computer,% to the average number of employees of enterprises by industry. The benefits of digital enterprise are identified, as well as five key components of digitalization in Ukraine. Priority directions for reducing the “digital” gap in domestic practice are presented. Emphasis is placed on the digital competence of employees. An important feature of the acquisition of digital competencies is the way they are acquired, which is different from traditional academic training of professionals: on-the-job training, separate on digital platforms as a source of value formation in the digital economy. The basic directions of development of digitalization of activity of domestic enterprises are substantiated. Attention is drawn to the obstacles to the widespread adoption of digital technologies in the activities of domestic enterprises. Ways of training and development of the personnel which influence on introduction of digital technologies in the enterprises of different branches are offered. It is concluded that the success of businesses will depend to a large extent on the “digital maturity” of staff, as well as their ability to use information using the appropriate digital technologies.